All Days 2014
DOI: 10.4043/24763-ms
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of the Steam-Assisted-Gravity-Drainage Process in Offshore Heavy Oil Reservoirs with Bottom Water

Abstract: Due to the water-coning problem, cycle steam stimulation (CSS) in the heavy oil reservoirs with bottom water is often less effective, and the oil recovery is even below 10%. Steam assisted gravity drainage (SAGD) is the oil-producing process with a constant pressure-drop (about 0.30 MPa), and it is a potential technique for this reservoirs. Through the implementation of SAGD, bottom water could be effectively controlled. Aiming at the LD heavy oil block in Bohai offshore oilfield, the SAGD performance in heter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 7 publications
(9 reference statements)
0
4
2
Order By: Relevance
“…Figure 8 reveals that the oil recovery factor and cumulative energy injected into the oil reservoir without a bottom water zone are lower than those occurring in reservoirs with a bottom water zone due to the bottom water augmenting the expansion process of the steam chamber in the oil pay zone, as indicated in Figure 9. This result is opposite to that of the previous study [26], which showed that the oil recovery factor is reduced by 10% with the bottom water zone. This difference occurs mainly because, in the previous study, no solution gas was considered in the heavy oil so that the heat transfer rate would not be reduced and the steam chamber could extend freely [26].…”
Section: Effect Of Thickness Of the Bottom Water Zonecontrasting
confidence: 57%
See 2 more Smart Citations
“…Figure 8 reveals that the oil recovery factor and cumulative energy injected into the oil reservoir without a bottom water zone are lower than those occurring in reservoirs with a bottom water zone due to the bottom water augmenting the expansion process of the steam chamber in the oil pay zone, as indicated in Figure 9. This result is opposite to that of the previous study [26], which showed that the oil recovery factor is reduced by 10% with the bottom water zone. This difference occurs mainly because, in the previous study, no solution gas was considered in the heavy oil so that the heat transfer rate would not be reduced and the steam chamber could extend freely [26].…”
Section: Effect Of Thickness Of the Bottom Water Zonecontrasting
confidence: 57%
“…This result is opposite to that of the previous study [26], which showed that the oil recovery factor is reduced by 10% with the bottom water zone. This difference occurs mainly because, in the previous study, no solution gas was considered in the heavy oil so that the heat transfer rate would not be reduced and the steam chamber could extend freely [26]. Therefore, the pressure in the steam chamber was not maintained, and the steam could be injected continuously.…”
Section: Effect Of Thickness Of the Bottom Water Zonecontrasting
confidence: 57%
See 1 more Smart Citation
“…Preheating phase aims to create thermal interconnection between producer well and injector well. There are three approaches, including cyclic steam stimulation, steam circulation and fracturing (Liu 1998;Dong et al 2014). In this model, the CSS preheating method is adopted.…”
Section: Simulation Modelmentioning
confidence: 99%
“…They considered the steam channeling phenomenon among vapor chambers. Dong et al (2014) numerically studied the SAGD performance in a heterogeneous heavy oil reservoir with bottom water. Using CMG-STARS thermal simulator, Hashemi-Kiasari et al (2014) studied the effect of operational parameters on SAGD performance in a dip heterogeneous naturally fractured reservoir.…”
Section: Introductionmentioning
confidence: 99%